Changes in the indicators of connective tissue metabolism in the blood serum of experimental rats under the conditions of modeling the development of degenerative processes in paravertebral muscles - Radchenko, Volodymyr; Leontyeva, Frieda; Tuliakov, Vladyslav; Skidanov, Mykyta; Nikolchenko, Olga; Skidanov, Artem (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
Low back pain is a common health problem. To deepen the understanding of the pathogenesis of the disease, experimental studies on animals with modeling of the pathological process are necessary. Objective. Based on the analysis of biochemical markers of connective tissue metabolism in the blood serum of laboratory rats, the applicability of the studied models of degenerative muscle tissue damage to study the relationship between this condition and the development of disorders in spinal motor segments was assessed. Methods. Two models of reproduction of degenerative processes in the paravertebral muscles of white rats were tested: I (n = 5) — alimentary (diet-induced) obesity, by keeping it for 3 months on a high-calorie diet; II (n = 5) — ischemia, by tying the large rectus muscles of the back with suture material (45 days). Control group (n = 5) — intact animals of similar age and sex. The content of glycoproteins, total chondroitin sulfates (CS), hexosamines, protein-bound hexoses, seroglycoides, fractional distribution and total content of hydroxyproline and glycosaminoglycan sulfates (GAGs) were investigated in the blood serum of rats. The results. In the blood serum of rats of groups I and II, a significant increase compared to the control level of glycoproteins was determined, with a greater effect in the ischemia model, but no significant changes of protein-bound hexoses, hexosamines and CS were recorded. The level of inflammatory markers (sialic acids and seroglycoides) in the blood serum of animals of both groups did not differ significantly from the control, and changes in the parameters of hydroxyproline (except for the slightly changed protein-bound fraction) and GAGs were significant only for the ischemia model. Conclusions. Based on the analysis of biochemical markers of connective tissue metabolism in rats of groups I and II, changes characteristic of degenerative processes were determined, with a greater manifestation in the ischemia model. No significant increase in biochemical markers of inflammation was recorded. Both models can be used to reproduce dystrophic processes in osteochondrosis.